The perception of students towards ChatGPT in the University of Bengkulu: A descriptive study - Annur, Yusri Fajri; Sujarwati, Iis (Universitas Katolik Widya Mandala Surabaya, 2023)
The rapid advancement of AI technologies, particularly ChatGPT, is reshaping the educational landscape. Understanding how students perceive these technologies is crucial for their effective integration into academic environments. This study aims to investigate students' perceptions of ChatGPT's role in supporting academic tasks, such as learning, research, and assignments at the University of Bengkulu. A descriptive survey design was employed, utilizing structured questionnaires based on the Technology Acceptance Model (TAM). Responses from 75 students across various faculties were analyzed using descriptive statistics and ANOVA to explore perceptions regarding ChatGPTs usefulness, ease of use, and ethical considerations. The results indicate that students view ChatGPT as moderately useful, particularly for saving time on assignments and research tasks. However, there are ethical concerns, notably about plagiarism, and a demand for better training on the ethical use of AI. ChatGPT is perceived as a valuable tool in enhancing academic efficiency, but there is a need for comprehensive training to address ethical challenges in its use.